Analisis Pendapatan Rumah Tangga dari Tanaman Kelapa di Desa Rebo Kecamatan Sungailiat Kabupaten Bangka - Karsiningsih, Eni; Evahelda, .; Saputra, A (ENVIAGRO, 2010)
The purpose of this research are to (1) knowing coconut production per month that prodused by household, (2) Calculate household income received from the sale of coconut, (3) Calculate the distribution of coconut revenue to total household income.  Research is done in village district Rebo district Sungailiat Bangka with time data acquisition at the start of the month of February until march 2010.  Research method used is survey method with sampling method using  simple random sampling of 30 household with population of  250 household.  Result showed that the average amount of coconut production is 467 pieces per month per hectare.  Household income from selling the coconut is Rp 437.424,89 per hectare.  Coconut revenue contribution to total household income is 25,23 persent per month per hectare.